2014
DOI: 10.31018/jans.v6i2.504
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different modes of pollination on quantitative and qualitative parameters of Egyptian Clover, Trifolium alexandrinum L.

Abstract: Abstract:The effect of different modes of pollination on quantitative and qualitative parameters of Egyptian clover, Trifolium alexandrinum L. was studied at Forage Section, Department of Genetics and Plant Breeding, CCS, Haryana Agricultural University, Hisar during 2012 and 2013. Maximum seed setting (81.5%) was recorded in A. mellifera pollination with an 8 frame colony (BP-8F) followed by 4 frame colony (BP-4F) (75.1%), open pollination (OP) (73.8%) and 2 frame colony (BP-2F) (71.5%). Maximum seed yield (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 3 publications
2
6
0
Order By: Relevance
“…Our results here were harmony with these gained by Free, 1993 who revealed that higher 1000-seed weight heads in bee pollination plots by 13.8 g compared to 0.2 g in without insect pollination but was significantly lower in op 6.1 g. Also, Jat et al (2014) involved the treatment BP-4F, BP-2F and op significantly heavier than without insect pollination (3.30, 3.17 and 3.03 g, respectively) in seed weight.…”
Section: -1000-seed Weightsupporting
confidence: 92%
See 3 more Smart Citations
“…Our results here were harmony with these gained by Free, 1993 who revealed that higher 1000-seed weight heads in bee pollination plots by 13.8 g compared to 0.2 g in without insect pollination but was significantly lower in op 6.1 g. Also, Jat et al (2014) involved the treatment BP-4F, BP-2F and op significantly heavier than without insect pollination (3.30, 3.17 and 3.03 g, respectively) in seed weight.…”
Section: -1000-seed Weightsupporting
confidence: 92%
“…The obtained data are in agreement with what reported by Jat et al (2014) and Bondok et al (2016) whom mentioned that, high seed setting may be attributed to the role of honeybees density per unit area as an agent of pollination where honey bees are the major factor causing seed setting in the Egyptian clover.…”
Section: -Seed Setting and Fertility Indexsupporting
confidence: 92%
See 2 more Smart Citations
“…The minimum seed yield of (5.26 q ha -1 ) was obtained in the plots treated with B. bassiana 1.15 WP followed by the treatment neem leaf extract (6.10 q ha -1 ) which was found statistically at par with each other. Jat et al (2012), Chandel et al (2014), Sharma et al (2014) reported that the highest yield was recorded in spinosad 0.01 per cent followed by indoxacarb 0.01 per cent plot.…”
Section: Effect Of Insecticides and Biopesticides On The Seed Yield O...mentioning
confidence: 97%